Integrating case-based learning with collective reflection: outcomes of inter-professional continuing education. Issue 1 (2nd January 2019) - Golaghaie, Farzaneh; Asgari, Shadi; Khosravi, Sharareh; Ebrahimimonfared, Mohsen; Mohtarami, Abolfazl; Rafiei, Fatemeh
ABSTRACT: This study was conducted to identify the effect of integrating case-based learning with reflection on the outcomes of continuing nurse education. An experimental study with pre/post design was performed. Eighty participants were allocated to one of the two educational groups using cluster randomization. In the experimental group, the medical information of real patients, and the didactic components regarding the management of such cases was presented. Then, the participants were guided to perform a collective reflection on patient care, based on the Driscoll᾿ Model of Structured Reflection, including description, analysis, and proposed actions. In the other group, the traditional lecture method was applied by the same educators. After controlling the pre-test scores, the ANCOVA revealed a significant difference in the post-test mean score of learning ( F = 11.54, p < 0. 01, η 2 p = 0.13) and self- perceived competency ( F = 29.54, p < 0.001, η 2 p = 0.28). There was no significant difference in the participants' reaction to the program between the groups. This study showed that integrated case-based reflection promoted the participant's learning and self-perceived competency through continuing education.